Colonic polyps in Nigerians, a change in trends: A retrospective single‑center clinicopathological study (2022)
Background: Adenomatous polyps in the colon are recognized precursors of colorectal carcinoma; however, the low incidence of these polyps in sub Saharan Africans has led many to believe that the pathway of colorectal cancer may differ in this region. The objective of this study was aimed to determine the change in trends of colonic polyps in Nigeria. Methods: This was a 10 year retrospective review of all colonic polyp specimens received at the Department of Pathology in our hospital utilizing the histopathology request cards and hematoxylin and eosin stained slides. The data were analyzed using the IBM SPSS Statistics (version 23; IBM Corporation, Armonk, New York, USA). Results: A total of 131 cases were reviewed. The age of patients ranged from 5 to 86 years with a mean age of 55 years. The male to female ratio was 1.6:1. The mean age was 59.4 years. Of the 131 cases reviewed, 62 patients had adenomatous polyps, 49 had inflammatory polyps while 20 others included juvenile polyps, hyperplastic polyps, and hamartomatous polyps. Conclusion: Adenomatous polyps are increasingly being seen among Africans in the sub Sahara region and perhaps they are not as rare as it was once thought provided the facilities for the diagnosis are available. They may yet play a more important role than has been ascribed to them in the pathogenesis of colorectal carcinomas in Africans.